A brain-enriched circular RNA controls excitatory neurotransmission and restricts sensitivity to aversive stimuli - Giusti, Sebastian Alejandro (2024)
Circular RNAs are a large class of non-coding RNAs present in all eukaryotic taxa. Despite the identification of thousands of circular transcripts, the biological significance of most of them remains largely unexplored, partly due to the lack of effective methods for generating loss-of-function animal models. In this study, we focused on circTulp4, a highly abundant circRNA that is enriched in the brain and synaptic compartments. By creating a circTulp4-deficient mouse model, in which we mutated the splice acceptor site responsible for generating circTulp4 without affecting the corresponding linear mRNA or protein levels, we were able to conduct a comprehensive phenotypic analysis. Our results demonstrate that circTulp4 is critical in regulating neuronal and brain physiology, modulating the strength of excitatory neurotransmission and sensitivity to aversive stimuli. This study provides compelling evidence that circRNAs can regulate biologically relevant functions in neurons, with modulatory effects at multiple levels of the phenotype, establishing a proof-of-principle for the regulatory role of circRNAs in neural processes.